(untitled) (Eurasian Research Bulletin, 2023)
Cardiovascular diseases (CVDs) remain a global health challenge, and recent research has illuminated the critical role of inflammation as a cardiovascular risk factor. This article explores the evolving landscape wherein inflammation transcends its traditional role as a localized immune response to emerge as a central player in the intricate pathogenesis of atherosclerosis—the underlying cause of most cardiovascular events. Chronic inflammation, once perceived as a secondary consequence, is now recognized as a systemic catalyst for atherosclerotic processes, initiating a cascade of events that transform endothelial cells, recruit immune cells, and contribute to plaque formation